A Systematic Literature Review: Challenges of Implementing Indonesian Language Proficiency Test for Students at Universitas Merangin - Aryanti, Puji Tri (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
The research was conducted to describe perspectives on the challenges of implementing the Indonesian Language Proficiency Test (UKBI) among students, especially at Universitas Merangin. The method used is a systematic literature review consisting of identification, screening, feasibility, quality assessment, and qualitative synthesis. The results of the research show that: 1) Complete and comprehensive information about UKBI has not reached the Universitas Merangin academic community properly, 2) There is no policy for higher education institutions to implement UKBI for students; 3) the Relevance of UKBI results to student needs; 4) The current UKBI is paid, so it doesn’t motivate students to take UKBI.